Brief Report: Association of Adipokines With Bone Mineral Density in HIV-Infected and HIV-Uninfected Women. (1st December 2016) - Sharma, Anjali; Ma, Yifei; Scherzer, Rebecca; Wheeler, Amber L.; Cohen, Mardge; Gustafson, Deborah R.; Keating, Sheila M.; Yin, Michael T.; Tien, Phyllis C.
Abstract : Background: HIV infection is associated with low bone mineral density (BMD) and alterations in adipokines, which may mediate the relationship between fat and bone. Objective: To evaluate the relationship of adiponectin and leptin with BMD in HIV-infected and uninfected women. Methods: We measured BMD over 5 years at the lumbar spine, total hip (TH), and femoral neck (FN) using dual-energy X-ray absorptiometry in 318 HIV-infected and 122 HIV-uninfected participants of the multicenter Women's Interagency HIV Study (WIHS). Total adiponectin and leptin were assayed on stored sera. Multivariable linear mixed models assessed the effects of adipokines and HIV status on BMD. Results: HIV-infected women had higher adiponectin (median 6.2 vs. 5.6 μg/mL, ) but lower leptin (11.7 vs. 19.8 ng/mL) levels at baseline (both P < 0.05) compared with HIV-uninfected women. HIV infection was associated with lower BMD at the lumbar spine (−0.074 g/cm 2 ), FN (−0.049 g/cm 2 ), and TH (−0.047 g/cm 2 ) (all P < 0.05) after adjusting for demographic, behavioral, and metabolic factors. HIV infection remained associated with lower BMD at each site, with little change in the effect sizes after additional adjustment for adiponectin or leptin. Among HIV-infected women, higher adiponectin was associated with lower TH BMD (−0.025 g/cm 2 per 10-fold increase, P = 0.035), whereas higher leptin was associated with higher BMD at FN (+0.027 g/cm 2 per 10-fold increase, P = 0.005) and TH (+0.019 g/cm 2, P = 0.028). After multivariable adjustment, the adipokines showed little association with BMD at any site ( P > 0.8 for adiponectin; P > 0.2 for leptin). Conclusions: Alterations in serum adiponectin and leptin do not explain low BMD in HIV-infected women.